Performing autobiography : contemporary Canadian drama - Stephenson, Jenn, 1971- (University of Toronto Press, 2013)
Stephenson explores the autobiographical form by analysing seven works by Canadian playwrights written and performed between 1999 and 2009, including Judith Thompson's Perfect Pie, Daniel MacIvor's In On It, and Timothy Findley's Shadows.